Using reclaimed water for golf course irrigation to improve water resource management in the Lower Arkansas River Basin - McCluskey, Kara M. (Kansas State University, 2015)
With an increasing population, municipalities in the United States are struggling to secure safe, reliable water sources for future water demands. Alternative water sources are being considered to improve the overall water management picture. Wastewater reuse, reusing wastewater effluent for beneficial purposes, is an alternative water source that is gaining popularity in the United States. In this study a theoretical framework was developed to enable a region to quickly assess the feasibility of reusing wastewater for irrigation needs. Three criteria were established for the framework; they are, regulations and guidelines for reuse, adequate flow ratio, and cost benefit analysis. As a region moves through the framework and criteria a list of feasible wastewater facilities and end users are established. A model was developed for the cost benefit analysis based on regional input. As regulatory frameworks and economic factors evolve over time the model can be updated to assess how these changes will affect water reuse in a region. The model will provide a useful tool for a region to integrate wastewater reuse into the water resource management process. The Lower Arkansas River Basin (LARK) was highlighted by the Kansas Water Office as a region that should investigate the role of reuse in water conservation. Results from this report indicate 963 million gallons per year (MG/yr) of wastewater effluent could feasibly be used to irrigate 9 hole and 18 hole golf courses in the region. The results determined that any 18 hole golf course within a 15.9 mile radius of a wastewater treatment facility in the LARK could payback the capital costs for wastewater reuse within 10 years. This information is a useful tool for the region to start the discussion for implementing wastewater reuse in the region. The results from this report indicate wastewater reuse for golf course irrigation is economically feasible in the LARK. Establishing a safe reliable water source for the future is paramount to the future of Kansas. Future research is needed to determine how the wastewater diversion affects the environmental balance of the permitted discharge location.
Keywords: Wastewater Reuse; Civil Engineering (0543); Water Resource Management (0595)